Uso de medicamentos, consumo alimentar e risco metabólico em mulheres portadoras de fibromialgia - FONTES, Ariadina Jansen Campos (2021)
Introduction: Fibromyalgia is a disease of unknown etiology, characterized by generalized pain, fatigue, sleep and mood changes, affecting mainly females. Due to the negative impact caused by fibromyalgia on the quality of life of patients with the disease, it is important to know which are the most used drugs and potential drug nutrient interactions, as well as nutritional inadequacies, probable metabolic risk and nutritional status of these individuals so that these are managed in order to avoid damage to health. Objective: To analyze medication use, nutrient consumption and metabolic risk in women with fibromyalgia. Methodology: This is an observational, cross-sectional study, carried out from September 2019 to February 2020 with 71 women with fibromyalgia treated at the Chronic Pain Outpatient Clinic, Pain House, of the University Hospital of the Federal University of Maranhão (HU-UFMA) in São Luís, Maranhão. The analysis of drug use was performed using the Pharmacotherapeutic Profile Questionnaire and the likely drug-nutrient interactions were searched in the Drugbank database. Nutrient intake was verified using the 24-hour recall with the aid of a photo album to standardize home measurements and the Avanutri Online software to quantify nutrient intake according to Dietary Reference Intakes (DRIs). The metabolic risk was was identified through anthropometric indicators of waist circumference (WC), neck circumference (NC), waist/height ratio (WHtR) and waist/hip ratio (WHR). Nutritional status was determined using the body mass index (BMI). Statistical analysis was descriptive and the Kolmogorov-Smirnov test was performed to verify the normality of numeric data, the results were described by frequencies, mean, standard deviation and percentiles using Stata version 14.0 with 5% α. Results: Participants were 45±9.95 years old. The most prevalent drugs were pregabalin 52.11%, duloxetine 23.35%, amitriptyline 16.90%, tramadol 16.90%, cyclobenzaprine 14.08%, paracetamol associated with codeine phosphate 5.63% and gabapentin 5.63%. Possible drug-nutrient interactions were found for almost all drugs mentioned, except for cyclobenzaprine. The intake of macronutrients was adequate according to the percentage values of the reference, despite this, there was a reduced consumption of most micronutrients, with the exception of vitamin B12 and phosphorus. The existence of metabolic risk was observed by WC 74.65%, WHR 53.52% and WHR 97.18%. The mean of IMC was 23.77±10.10, but there was a predominance in the classifications of overweight and obesity in 61.87% of the participants. Conclusion: Pregabalin and duloxetine were the drugs most used by womens with fibromyalgia, and potential drug-nutrient interactions were identified. The intake of macronutrients was adequate, however, the consumption of most micronutrients was found to be deficient. Most woman were at metabolic risk and although the eutrophy classification was obtained from the sample mean, there was a predominance of overweight and obesity.